One-dimensional freezing of seawater in a constrained volume - Szilder, Krzysztof; Lozowski, Edward P.; Forest, Tom W. (Canadian Geotechnical Journal, 1995)
A numerical time-dependent model of the one-dimensional fusion of seawater with limited salt rejection has been developed. The process of latent heat release, as brine cools and freezes, as well as changes of the specific heat capacity and thermal conductivity of sea ice with temperature have been incorporated into the model. The model predicts the variation of the brine temperature and the motion of the liquid–solid interface. Laboratory experiments have been performed to verify the model. Five centimetre layers of fresh water and brine of salinities 5, 10, 15, and 20%o were poured on an insulated surface and exposed to cold air from above. A comparison between the experimental results and the model prediction shows satisfactory agreement. Key words : sea ice, freezing, salinity, heat conduction, ice islands.